INTERAKSI SOSIAL DAN PELESTARIAN BUDAYA MASYARAKAT INDIA TAMIL DI KUIL SHRI MARIAMMAN KOTA MEDAN - Betaria Sihaloho; Rina Panggabean; Sri Sulastri Sitohang; Alan Mustaqim Nst; Ferdy Alamsyah; Rohani; Elsa Kardiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the importance of social interaction in maintaining the cultural identity of a multicultural society, specifically the Tamil Indian community in Medan City. The primary focus is to analyze the forms, patterns, and intensity of social interaction at Shri Mariamman Temple and its role in cultural preservation. Utilizing a qualitative approach with a case study method, data were collected through participant observation, in-depth interviews, and documentation. Findings reveal that social interactions are associative, characterized by strong kinship patterns and high intensity, particularly during religious festivals such as Thaipusam and Deepavali. These interactions effectively strengthen internal solidarity while fostering harmony with cross-ethnic communities in the Kampung Madras area. The discussion highlights that Shri Mariamman Temple serves as a social institution and a center for cultural transmission through the use of the Tamil language, ritual symbols, and the active involvement of the younger generation as an adaptation strategy against modernization. It is concluded that the temple plays a crucial role not only as a place of worship but as a medium for preserving a dynamic cultural identity within a multicultural society. The researchers suggest strengthening youth participation and utilizing digital technology to ensure the future sustainability of these traditions.